Simulating Business Activities In Investment Decisions - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
The risks and rewards of a proposed investment are measured by projecting financial performance of the investment in an assumed business environment. The validity of the assessment of the project's peiformance can be evaluated by examining the appropriateness of the business environment modeling and the peiformance of the investment in such a modeled environment. This article describes the application of simulation approach to measuring of rewards and risks in a decision making process for new investments. Specifically, this article provides a model that simulates conditions in. which a worst condition may threat a company to bankruptcy and the way to reduce such risk. Hypothetical data representing typical situations in investment decisions were used to illustrate the power and benefits of simulation. This simulation approach is intended to show how the conventional investment decision process can be improved through simulation.